Oil spill studies : healing the ocean, biomarking and the law - Muttin, Frédéric; Muttin, Frédéric (Elsevier Ltd. ; ISTE Press, 2018)
The containment of pollution by physical defenses is the first step in restoring the ocean to its natural state. The first two chapters of Oil Spill Studies: Healing the Ocean, Biomarking and the Law describes the feedback on seven experiments made on the East Atlantic Ocean. The first chapter concerns semi-open sites while the second focuses on open environment directly linked to the ocean. The third chapter examines pollution from a French harbor marina and its effects on the local biodiversity. The book provides a methodology to quantify biological contamination coming from heavy metal releases into the environment. Chapter four provides the state-of-the-art in the science of a mid-depth-living fish species affected by the treatment of oil pollution by chemical dispersion. In a similar way, the fifth chapter addresses new explored and exploited ocean with extreme environments such as the Arctic and deep sea. The sixth and final chapter provides a lawyer's analysis on the subject.